Ultrasensitive detection of disease biomarkers using an immuno-wall device with enzymatic amplification. Issue 15 (25th June 2019) - Nishiyama, Keine; Kasama, Toshihiro; Nakamata, Seiya; Ishikawa, Koya; Onoshima, Daisuke; Yukawa, Hiroshi; Maeki, Masatoshi; Ishida, Akihiko; Tani, Hirofumi; Baba, Yoshinobu; Tokeshi, Manabu
Abstract : We present a fluorometric sandwich immunoassay for biomarkers utilizing an antibody-modified microfabricated wall and antibody labeled with an enzyme for signal amplification. Abstract : We present an ultrasensitive immunoassay system for disease biomarkers utilizing the immuno-wall device and an enzymatic amplification reaction. The immuno-wall device consisted of 40 microchannels, each of which contained an antibody-modified wall-like structure along the longitudinal axis of the microchannel. The wall was fabricated with a water-soluble photopolymer containing streptavidin by photolithography, and biotinylated capture antibodies were immobilized on the sides through streptavidin–biotin interaction. For an assay, introducing the target biomarker and secondary and labeled antibodies produced a sandwich complex anchored on the sides of the wall. A conventional immuno-wall device uses a fluorescence-labeled antibody as a labeling antibody. To achieve an ultrasensitive detection of a trace biomarker, we used an enzyme label and amplified the signal with the enzymatic reaction with a fluorogenic substrate in the microchannel. The highest signal/background ratio was obtained by using alkaline phosphatase-labeled antibody and 9 H -(1, 3-dichloro-9, 9-dimethylacridin-2-one-7-yl) phosphate. To evaluate the device performance, we detected human C-reactive protein (CRP) as a model biomarker. The detection limit (LOD) of CRP in phosphate-buffered saline was 2.5 pg mL −1 with a sample volume of 0.25 μL. This LOD was approximately 3 orders of magnitude lower than that obtained with fluorescent-dye (DyLight 650)-labeled antibody. In addition, the present device provided a wide detection range of 0.0025–10 ng mL −1 for CRP. We successfully developed an ultrasensitive immunoassay system with simple operation and only a small sample volume.